2017
DOI: 10.15252/embr.201745497
|View full text |Cite
|
Sign up to set email alerts
|

Nup62‐mediated nuclear import of p63 in squamous cell carcinoma

Abstract: Nuclear pore complexes (NPCs) are multiprotein channels that bridge the nucleus with the cytoplasm and regulate all nucleo‐cytoplasmic traffic. NPCs are built by the repetition of ~30 different proteins known as nucleoporins (Nups). Accumulating evidence has revealed a diversity in NPC composition that is critical for cell‐specific functionality and fate determination. A new report by Hazawa et al now identifies the central transport channel nucleoporin Nup62 as a novel regulator of cell proliferation and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Of course, we cannot completely rule out the fact that some of the Kaps might translocate through phosphorylated NPCs at longer simulation times. Nevertheless, the trend of a reduced probability for active transport through phosphorylated pores and an increased probability for passive transport upon phosphorylation is in accordance with experimental observations [27,29,30,31,32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of course, we cannot completely rule out the fact that some of the Kaps might translocate through phosphorylated NPCs at longer simulation times. Nevertheless, the trend of a reduced probability for active transport through phosphorylated pores and an increased probability for passive transport upon phosphorylation is in accordance with experimental observations [27,29,30,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, there is evidence which confirms that FG-Nups undergo phosphorylation in vivo as well [21,23,27,28]. Transport studies demonstrated that the phosphorylation of nucleoporins results in decreased kinetics of active transport of Kap95 [25,27,29] and Kap-cargo complexes [30,31], and increased kinetics of passive transport [32]. These studies indicate that phosphorylation can modulate the selective permeability of the NPCs.…”
Section: Introductionmentioning
confidence: 92%
“…In upper vertebrates, the ZEB family includes two proteins, ZEB1 and ZEB2, which act as either transcriptional repressors or activators depending on the target gene and tissue. 60 [74][75][76][77][78] Indeed, altered ΔNp63 expression is also present in oral epithelial dysplasia, playing a potential role in malignant transformation of epithelial cells. 79,80 4.5 | Additional transcription factors E12 and E47, encoded by the E2A gene, belong to the same transcription factor family of Twist proteins.…”
Section: Zeb Familymentioning
confidence: 99%
“…While not covered exhaustively in this review, mechanisms including, but not limited to, stabilization, degradation, and cellular localization are involved in modulating ΔNp63α activity (reviewed in [45]). Recently described examples of additional mechanisms include interactions with syntaxin-binding protein 4 to suppress the proteolysis of ΔNp63α, leading to decreased turnover [46,47], and increased activity of the nucleoporin NUP62 to facilitate ΔNp63α nuclear import, potentiating its role as a transcription factor [48,49]. Differential methylation status of the ΔNp63α gene locus is also involved in driving its expression [26].…”
Section: Mechanisms Of Transcriptional Regulation By P63mentioning
confidence: 99%